Proses Berpikir Kritis Mahasiswa dalam Menyelesaikan Masalah Grup Berdasarkan Jenis Kelamin : The Students’ Critical Thinking Process in Solving Group Problems Based on Gender - Sa'adah, Nihayatus; Juniati, Dwi; Khabibah, Siti (Universitas Islam Jember, 2024)
This research aimed to describe students' critical thinking processes based on gender in solving group problems. The subjects were a boy and a girl with equal abilities. The instrument was a critical thinking test. Data were analyzed based on FRISCO indicators. The results are on the indicator of: (1) focus, the boy has difficulty in solving problems of power set context while the girl succeeds in any context; (2) reason, both subjects provide relevant reasons; (3) inference, the boy has difficulty in forming conclusions of power set context while the girl succeeds in all conclusions; (4) situation, the boy does not use mathematical concepts that are relevant to the problem of power set context while the girl does of any contexts; (5) clarity, the boy explains the conclusion of integers set context while the girl does in all contexts; (6) overview, the two subjects do not recheck. Keywords: group algebra, gender, the critical thinking process